Conceptual analysis of social responsibility of the person and its integration in pharmaceutical practice - N. O. Tkachenko; В. Р. Hromovyk (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
The modern development of the social policy of pharmaceutical organizations in Ukraine, focused on the needs of society, is characterized by the lag in practical implementation of appropriate social responsibility (SR) from the increased interest of pharmaceutical scientists in its various aspects. Issues of personal identity, its role and place in the system of socially responsible behavior of pharmaceutical organizations and the professional activity of pharmacists remain insufficiently studied.